Rivaroxaban for secondary stroke prevention in patients with embolic strokes of undetermined source: Design of the NAVIGATE ESUS randomized trial. (September 2016) - Hart, Robert G; Sharma, Mukul; Mundl, Hardi; Shoamanesh, Ashkan; Kasner, Scott E; Berkowitz, Scott D; Pare, Guillaume; Kirsch, Bodo; Pogue, Janice; Pater, Calin; Peters, Gary; Davalos, Antoni; et al.
Background: Embolic strokes of undetermined source comprise up to 20% of ischemic strokes. The stroke recurrence rate is substantial with aspirin, widely used for secondary prevention. The New Approach riVaroxaban Inhibition of Factor Xa in a Global trial versus ASA to prevenT Embolism in Embolic Stroke of Undetermined Source international trial will compare the efficacy and safety of rivaroxaban, an oral factor Xa inhibitor, versus aspirin for secondary prevention in patients with recent embolic strokes of undetermined source. Main hypothesis: In patients with recent embolic strokes of undetermined source, rivaroxaban 15 mg once daily will reduce the risk of recurrent stroke (both ischemic and hemorrhagic) and systemic embolism (primary efficacy outcome) compared with aspirin 100 mg once daily. Design: Double-blind, randomized trial in patients with embolic strokes of undetermined source, defined as nonlacunar cryptogenic ischemic stroke, enrolled between seven days and six months from the qualifying stroke. The planned sample size of 7000 participants will be recruited from approximately 480 sites in 31 countries between 2014 and 2017 and followed for a mean of about two years until at least 450 primary efficacy outcome events have occurred. The primary safety outcome is major bleeding. Two substudies assess (1) the relative effect of treatments on MRI-determined covert brain infarcts and (2) the biological underpinnings of embolic strokes of undetermined source using genomic and biomarker approaches. Summary: The New Approach riVaroxaban Inhibition of Factor Xa in a Global trial versus ASA to prevenT Embolism in Embolic Stroke of Undetermined Source trial is evaluating the benefits and risks of rivaroxaban for secondary stroke prevention in embolic strokes of undetermined source patients. Main results are anticipated in 2018.